Analisis Pertumbuhan dan Produktivitas Kelapa Sawit pada Variasi Kerapatan Tanam - Parwati, Wiwin Dyah Ully; Nadeak, Filemon Hepron; Kautsar, Valensi (Politeknik Negeri Lampung, 2024)
In oil palm growth, planting density has a sustainable impact on its productivity. To enhance the long-term growth and production yield of oil palm, it is crucial to consider the establishment of appropriate planting densities during the initial planting phase. This research explores the relationship between planting density and productivity, highlighting the importance of determining optimal plant densities for optimal yields. The study was conducted at the Muara Tawang Estate (MTNE) in Kapuas Hulu Regency, West Kalimantan Province. Two blocks of oil palm land with three different planting densities (130, 136, and 143 plants per hectare) were observed to understand the relationship between planting density and agronomic characteristics. Measurements were taken on plant height, frond length, petiole width, number of male and female flowers, and sex ratio. The analysis unveiled consistent trends in oil palm production, which varied based on planting density. Planting densities of 130 and 136 showed superior production trends compared to 143, with 136 demonstrating production increases ranging from 19.8% to 29.8% relative to density 143, alongside enhancements in plant height and frond length by 4.6% and 5.4%, respectively. Additionally, petiole thickness and width were notably lower in density 143, experiencing reductions of 8.0% and 11.0%, respectively, compared to density 136, while the sex ratio exhibited a similar pattern, declining by 34.0% in density 143 compared to 136. This highlights the importance of determining appropriate planting densities to enhance oil palm productivity.